Practicing food anxiety: Making Australian mothers responsible for their families’ dietary decisions - Peterson, A.; Tanner, C.; Fraser, Suzanne (Routledge, 2014)
Concerns about the relationship between diet, weight, and health find widespread expression in the media and are accompanied by significant individual anxiety and responsibilization. However, these pertain especially to mothers, who undertake the bulk of domestic labor involved in managing their families’ health and wellbeing. This article employs the concept of anxiety as social practice to explore the process whereby mothers are made accountable for their families’ dietary decisions. Drawing on data from an Australian study that explored the impact of discourses of childhood obesity prevention on mothers, the article argues that mothers’ engagements with this value-laden discourse are complex and ambiguous, involving varying degrees of self-ascribed responsibility and blame for children's weight and diets. We conclude by drawing attention to the value of viewing food anxiety as social practice, in highlighting issues that are largely invisible in both official discourses and scholarly accounts of childhood obesity prevention.